2022
DOI: 10.3389/fsufs.2022.969503
|View full text |Cite
|
Sign up to set email alerts
|

Advances in application of ultrasound in meat tenderization: A review

Abstract: Tenderness could measure the eating quality of meat. The mechanism of muscle tenderization is becoming more and more critical in the past decade. Since the transforming of muscle into edible meat requires a complex physiological and biochemical process, the related tenderization of meat can be beneficial to improving the meat quality. As a non-thermal processing technology with energy-saving, environmental protection, and intense penetration, ultrasonic treatment has been widely used in the tenderizing process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 160 publications
0
10
0
Order By: Relevance
“…Ultrasonic treatment can cause structural changes in meat due to disruption of weak intermolecular forces [41] , damage to cell membrane proteins that weaken muscle tissue due to separation of Z and M line, degradation of desmin and troponin-N [11] ; and increase in the degree of proteolysis due to the release of proteases such as lysosomal cathepsins and intracellular Ca2+ [29] . Ultrasound causes conformational changes in actomyosin (reduction of alpha helix), modifying the hydrophobicity of the proteins and the content of sulfhydryl groups [42] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonic treatment can cause structural changes in meat due to disruption of weak intermolecular forces [41] , damage to cell membrane proteins that weaken muscle tissue due to separation of Z and M line, degradation of desmin and troponin-N [11] ; and increase in the degree of proteolysis due to the release of proteases such as lysosomal cathepsins and intracellular Ca2+ [29] . Ultrasound causes conformational changes in actomyosin (reduction of alpha helix), modifying the hydrophobicity of the proteins and the content of sulfhydryl groups [42] .…”
Section: Resultsmentioning
confidence: 99%
“…As the power of US increases, a positive effect on meat tenderness but greater lipid oxidation has been reported, while prolonged treatment times reduce the enzymatic activity of proteases, negatively affecting tenderness [9] , [10] . High ultrasonic powers can also produce undesirable effects such as protein denaturation and aggregation [11] . A variable that should receive special attention is meat packaging, since polymeric compounds can degrade, decreasing in molecular weight and intrinsic viscosity due to the effect of ultrasound [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that the mechanical effect of ultrasonic cavitation might be the direct reason for promoting texture properties. In the process of ultrasound‐assisted pickling, the myofibrils of pork were destroyed and their structure broken, causing the increased fragmentation index of myofibrils, due to the cavitation and mechanical effects produced by ultrasonic waves 34‐36 . Another study reported that myofibril disintegration released proteases, which degraded myofibrillar protein and weakened connective tissue 35,37 .…”
Section: Resultsmentioning
confidence: 99%
“…In the process of ultrasound-assisted pickling, the myofibrils of pork were destroyed and their structure broken, causing the increased fragmentation index of myofibrils, due to the cavitation and mechanical effects produced by ultrasonic waves. [34][35][36] Another study reported that myofibril disintegration released proteases, which degraded myofibrillar protein and weakened connective tissue. 35,37 In this study, the treatment (TSIU with 101.3 W L −1 ) can effectively ameliorate the texture properties of pork tenderloin.…”
Section: Effect Of Ultrasound-assisted Pickling On Texturementioning
confidence: 99%
“…Meat tenderization is a complex process that involves several sub-mechanisms, including aging-related chemical and structural changes, post-slaughter breakdown of myofibrillar proteins, breakdown of collagen, reduction of muscle fiber bundle diameter, and changes in sarcomere length during rigor mortis [10]. The concept mainly applies to red meat due to its high toughness (beef, mutton, horse, pork, buffalo, and lamb), and is minimally related to white meats such as chicken and fish [5,25].…”
Section: Introductionmentioning
confidence: 99%